"Parent Leadership and Voice": How Mid-Level Administrators Appropriate Pre-Kindergarten Parent Involvement Policy. Issue 7 (November 2021) - Wilinski, Bethany; Morley, Alyssa
In the United States, where public pre-K has recently undergone rapid expansion, pre-K policies often include a mandate for parent involvement. We analyze a pre-K parent involvement policy in the state of Michigan, demonstrating the ways mid-level administrators appropriated the policy. We show how the silences and tensions embedded in the policy became visible as the policy was appropriated by these actors. We argue that while the policy sought to "empower" parents, it simultaneously created subject positions that reified traditional notions of desirable parent involvement. This study points to the need for policies that address the complex nature of parent involvement and the importance of understanding the role of mid-level actors in policy appropriation.